Flexible self-charging lithium battery for storing low-frequency mechanical energy. (April 2022) - Yu, Shengrui; Ling, Yan; Sun, Shuang; Wang, Yunming; Yu, Zhaohan; Zheng, Jiaqi; Liu, Guang; Chen, Dan; Fu, Yue; Liu, Yang; Zhou, Huamin
Abstract: Flexible self-charging power source, with admirable capability to harvest/store the energy generated by human motion, is considered as the most suitable power supply for next generation of wearable electronic devices. Herein, we demonstrated a flexible self-charging lithium battery for storing low-frequency tiny motion energy. The electrospinning polyvinylidene fluoride-trifluoro ethylene (P(VDF-TrFE)) porous membranes was adopted as a piezoelectric separator and a supporting layer of the electrode to fabricate a novel flexible self-charging power cell (SCPC). The flexible SCPC could be effectively charged by directly collecting movement energy through mechanical deformation. The SCPC sealed in flexible case could be charged via periodic tapping (6 N, 1 Hz), indicating a storage capacity of 0.092 μA h in 330 s. Compared with traditional self-charging batteries, the flexible SCPC can work effectively at lower frequency and pressure, and collect the tiny motion energy of human body to power wearable electronic devices. This work may provide an innovative way to develop new self-charging wearable electronic devices. Graphical Abstract: A flexible self-charging lithium battery for storing low-frequency tiny movement energy has been realized basing on electrospinning P(VDF-TrFE) nanofiber film. And the self-charging battery can work effectively at lower frequencies and pressures (6 N 1 Hz), showing a storage capacity of 0.092 μA h within 330 s ga1 Highlights: The flexibility is attributed to the integrated structure of electrode and separator. Unique hierarchical porous structure facilitates to collect tiny movement energy. The storage capacity reached 0.092 μA h within 330 s by compression deformation.